Chlorhexidine Improves Hygiene Reducing Oral Polymorphonuclear Leukocytes with Antimicrobial Effects at Distinct Microenvironments amongst Subjects Stratified by Health Status - Prem K. Sreenivasan; Violet. I. Haraszthy (MDPI AG, 2022)
Oral conditions such as gingivitis and oral malodor are commonly reported globally. Objective: This investigation clinically stratified subjects to healthy, malodor and gingivitis groups and enumerated oral polymorphonuclear leukocytes (PMN) as a measure of inflammation prior to and after rinsing with a chlorhexidine (CHX) mouthwash. The study also assessed clinical outcomes (dental plaque and gingival bleeding indices), malodor (halimeter scores, organoleptic and tongue coat index and microbiological parameters (anaerobic and malodor organisms of dental plaque, tongue surface and saliva) for a comprehensive assessment of the oral inflammatory burden. Methods: Consenting adults were stratified into control (n = 17), gingivitis (n = 19) and halitosis (n = 17) groups based on clinical criteria. At baseline, oral samples were examined for PMN in addition to microbiological analysis of dental plaque, saliva and tongue scrapings for anaerobic and malodor bacteria. Subjects were issued a commercially available fluoride toothpaste and a chlorhexidine mouthwash for two-week use prior to post-treatment assessments identical to baseline. Results: At baseline, PMN were lowest in the control that increased amongst the halitosis subjects, with the gingivitis group registering the highest levels (p < 0.05) with these outcomes corresponding with clinical parameters (p < 0.05). CHX use improved outcomes with a 56-61% reduction in PMN with significant differences between groups (p < 0.05). Dental plaque and bleeding indices were lower by 57-78% with oral malodor, demonstrating reductions of 33-59% (p < 0.05). Significant reductions in anaerobic and malodor organisms ranging from 78-96% and 76-94%, respectively, were noted after CHX use (p < 0.05). Conclusions: At study enrollment, PMN scores were lowest in healthy subjects, with increasing numbers amongst halitosis followed by gingivitis. Amongst all subject groups, CHX use significantly reduced oral PMN and corroborated with corresponding decreases in clinical, malodor and bacterial outcomes. Together, these results demonstrate the significant reductions in the oral inflammatory burden following CHX use.